HIV-1 resistance mutations and genetic diversity among children failing antiretroviral treatment in five healthcare facilities in Benin, West Africa - Edwige Hermione Dagba Gbessin; Edmond Tchiakpe; René Kpemahouton Keke; Nicole Vidal; Michel Kiréopori Gomgnimbou; Haziz Sina; Euloge Senan Adjou; Aldric Afangnihoun; Moussa Bachabi; Akadiri Yessoufou; Abdoul-Salam Ouedraogo; Lamine Baba-Moussa (PLoS ONE, 2025)
Background Antiretroviral treatment increases the risk of accumulation of resistance mutations that negatively impact the possibilities of future treatment. This study aimed to present the frequency of HIV-1 antiretroviral resistance mutations and the genetic diversity among children with virological failure in five pediatric care facilities in Benin. Methods A cross-sectional study was carried out from November 20, 2020, to November 30, 2022, in children under 15 years of age who failed ongoing antiretroviral treatment at five facilities care in Benin (VL > 3log10 on two consecutive realizations three months apart). Viral loads were measured using the m2000 RealTime Abbott platform. Genotyping was carried out with the commercial Viroseq kit. Sequences were read on the ABI 3500 sequencer and then edited with ViroSeqHIVv3.0 software. The HIV drug resistance database at Stanford University was used to identify mutations and viral subtypes were assigned by phylogenetic analyses. Results The HIV-1 pol gene was sequenced in 47 participants with virological failure of antiretroviral treatment. The median age was 120 [Interquartile Range 90–144] months. The prevalent treatment was EFV base regimen (22/47; 46.8%). Median viral load was 4.39 log10 [IQR 3.81–4.86 log10] respectively. Resistance testing was successful among (37/47; 78.72%) children, resistance mutations were detected in (32/37; 86.48%) children, and (29/32; 90.62%) had at least one surveillance drug resistance mutation. Respectively (25/32; 78.12%), (28/32; 87.5%), (4/32; 12.90%), (22/32; 68.75%) had at least one resistance mutation associated with NRTIs, NNRTIs, PIs and NNRTIs+NRTIs. (12/32; 37.5%) of children carried mutations related to TAMs. the most frequently NRTIs identified were M184V (21/62; 33.9%) followed by TAMs (20/62; 32.2%) and T69G/D (2/62; 3.2%)s. Among mutations associated with NNRTIs K103N represented (18/64; 28.1%) followed by P225H (7/64; 10.9%). The I54V (3/6; 50%) mutation is the major PI observed. Genetic diversity is characterized by a preponderance of CRF02_AG (72%, 23/32), followed by unique recombinant forms (URFs) (25%, 8/32) and one subtype G. Conclusion A high rate of mutations has been observed in children. These data underline the importance of implementing routine genotypic testing in the biological monitoring of infected children to anticipate the accumulation of resistance mutations and thus compromise the treatment options available in Benin.